Peran Kepuasan Wajib pajak Sebagai Pemediasi Atas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak - Bahri, Samsul; Djaddang, Syahril; Widyastuti, Tri (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
Increasingly rapid economic development resulted in many new companies springing up and creating a tight business competition. To be able to maintain business continuity, companies must be able to make a careful planning and control of the costs. Planning and control can be realized with the budget as a mean of control. Controlling costs by the company are intended to enable companies to minimize costs. At minimal costs the company will be able to achieve the profit target by more optimal as primary destinations in general. In connection to this, the purpose of this study was to determine the costs of the company budget preparation, budget realization costs and revenues, as well as the role of the budget as a mean of control in achieving its profit target. The research was conducted at PT ABC located in Bogor. PT ABC is one of the private companies engaged in construction services focusing on building the types of housing. This kind of development focus includes the construction of a building without infrastructure development. The study of PT ABC shows that the preparation of the company's budget is based on field survey and accompanying informations on the revenue budget and previous projects. In the implementation of the work there was an increase in the actual cost, thus resulting difference in the budget and actual costs. The occurrence of this difference will reduce the company’s profits. Overall budgets have created optimal control of the realization of the costs incurred. Budget serves as guidelines and benchmarks maximum value in any cost incurred by the company. However, in the implementation of the work there are still some shortcomings, resulting cost difference persists. This difference occurs because lack of oversight of the usage of raw materials. Companies must be able to improve control over the using of raw materials to be better coordinated. Increased control is evidenced by the increase in its profit target achievement on the next project. In the subsequent project, company managed to improve the performance of surveillance so that the difference in costs declined and its optimal profit target can be achieved.